2016
DOI: 10.1177/0194599816674658
|View full text |Cite
|
Sign up to set email alerts
|

Are All Manikins Created Equal? A Pilot Study of Simulator Upper Airway Anatomic Fidelity

Abstract: This study evaluates the anatomic fidelity of several commercially available pediatric and adult manikins, including airway task trainers, which could be used in aerodigestive procedure training. Twenty-three experienced otolaryngologists assessed the aerodigestive anatomy of 5 adult and 5 pediatric manikins in a passive state, using rigid and flexible endoscopy. Anatomic fidelity was rated on a 5-point scale for the following: nasal cavity, nasopharynx, oral cavity, oropharynx, larynx, trachea, esophagus, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Woo et al 8 used a Likert scale–based questionnaire to evaluate the anatomic fidelity of several upper airway simulators and concluded that the AirSim Multi simulator was the most anatomically realistic. Similarly, in our study, in the face validity questionnaire completed by our group of experts, the score for anatomy realism for this simulator was high (4.1/5; Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Woo et al 8 used a Likert scale–based questionnaire to evaluate the anatomic fidelity of several upper airway simulators and concluded that the AirSim Multi simulator was the most anatomically realistic. Similarly, in our study, in the face validity questionnaire completed by our group of experts, the score for anatomy realism for this simulator was high (4.1/5; Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several models of upper airway examination are currently available on the market 8 . Medium‐fidelity simulators provide no indication of how well the procedure is being carried out, and so it is necessary to have professional supervision, which limits the time available for and increases the cost of practical training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 8 Simulators may be a helpful alternative to practice complex procedures, including intubation, without harming or endanger patients. 5 , 9 , 10 A high simulator quality and fidelity (degree of exactness with which something is reproduced) are vital for effective medical education and clinical training in neonatology. 11 14 …”
Section: Introductionmentioning
confidence: 99%